ALCOHOL CONSUMPTION AMONG FIRST AND SECOND-YEAR UNIVERSITY STUDENTS IN NOVI SAD - Ostojić, Zorana; Čanković, Dušan; Ukropina, Snežana; Čanković, Sonja; Tomašević, Tanja; Radić, Ivana (Acta medicae Medianae, 2025)
Alcohol is the most consumed psychoactive substance worldwide. The aim of this study was to assess the prevalence of alcohol consumption among university students in Novi Sad and the association of socioeconomic characteristics and psychoactive substance use with alcohol consumption. The study was a cross-sectional survey of University of Novi Sad students in 2019, as part of the project “Health behaviours of students: benefits and risks” funded by the Provincial Secretariat for Higher Education and Scientific Research. The research involved 664 students from thirteen faculties. The study instrument was an online questionnaire, and alcohol consumption was classified by daily intake units. The association of socioeconomic characteristics and psychoactive substance use with alcohol use was analyzed using the Chi-square or Fisher’s exact test. Two of five students drank alcohol more than once a month (43.2%), and only 15.5% reported that they had never drunk alcohol. Half of the students (50.2%) reported binge drinking, with a higher prevalence among men than women (64.2% vs. 44.1%) (p < 0.001). Approximately 4% (3.8%) of students believed that peer influence led them to drink more alcohol than they otherwise would have, with a higher prevalence among young men than women (7.0% vs. 2.4%) (p < 0.001). The prevalence of heavy drinking and binge drinking was higher among smokers and illicit drug users (p < 0.001). The prevalence of alcohol use and binge drinking among university students in Novi Sad is high. Peers have a negative influence on student alcohol use. Heavy drinking and binge drinking were more prevalent among smokers and illicit drug users.